Rancang Bangun Prototype Monitoring Ketidakseimbangan Beban Pada Transformator Distribusi Berbasis Internet Of Things - Zulfitra Zulfitra; Dadan Ramdan; Syarifah Muthia Putri (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
The Unbalanced load with a significant difference in the electricity distribution system causes the emergence of a neutral current, causing losses due to the flow of neutral current to the ground, overheating in one phase, and resulting in a decrease in quality and damage to the distribution transformer if it lasts for an extended period of time. The goal of this research is to design and build a monitoring prototype for measuring current, voltage, and percentage of unbalance on a distribution transformer prototype, with the goal of providing measurement data from the prototype via the internet. The Arduino Uno serves as a data processor from current and voltage sensors, and the ESP8266-01 serves as a wifi module, sending current measurement data for each phase, line to neutral voltage, and the percentage of load imbalance to the Thingspeak Web Server in the form of seven graphic displays that PC/ smartphone users can access online. The overall performance of this tool can work well by improving the measurement accuracy of the current sensor SCT 013-000 using a tuning approach, so that the resulting error meets the standard error of the measuring instrument.